2013
DOI: 10.2174/1874210601307010076
|View full text |Cite
|
Sign up to set email alerts
|

Dental Stem Cells and their Applications in Dental Tissue Engineering

Abstract: Tooth loss or absence is a common condition that can be caused by various pathological circumstances. The replacement of the missing tooth is important for medical and aesthetic reasons. Recently, scientists focus on tooth tissue engineering, as a potential treatment, beyond the existing prosthetic methods. Tooth engineering is a promising new therapeutic approach that seeks to replace the missing tooth with a bioengineered one or to restore the damaged dental tissue. Its main tool is the stem cells that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
0
32
0
3
Order By: Relevance
“…Human GF in many studies reported that they meet the criteria of mesenchymal stromal progenitor/stem cells . Fournier et al isolated GF colonies and reported their differentiation potential in three different lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human GF in many studies reported that they meet the criteria of mesenchymal stromal progenitor/stem cells . Fournier et al isolated GF colonies and reported their differentiation potential in three different lineages.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate ECM signal can direct GF to form hard tissue through expression of mRNA for alkaline phosphatase and bone morphogenetic protein 2/4 (BMP2/4) . In addition, it has been reported that each fibroblast culture contains a small proportion of mesenchymal stem cells (MSCs) without undergoing an enrichment selection procedure . Many in vitro studies reported significant periodontal regeneration using gingival mesenchymal stem cells (GMSC) .…”
Section: Discussionmentioning
confidence: 99%
“…No existen fuentes consistentes de células madre epiteliales generadoras de esmalte en el humano adulto (14,28) y probablemente este sea el factor limitante más importante en la elaboración de un biodiente (15,29,30); sin embargo, actualmente se investiga arduamente estas posibles fuentes celulares. Así, ciertos tejidos orales postnatales podrían emplearse como fuente de células epiteliales, entre los que incluye células madre progenitoras del epitelio oral (OESCs); los restos epiteliales de Malassez (ERM) presentes en el ligamento periodontal (PDL) en la vaina epitelial radicular de Hertwig cerca de los extremos de una raíz en formación; en el epitelio reducido del esmalte (REE) que cubre el esmalte durante la erupción dental; el epitelio de unión (JE) a nivel del cuello dentario; la lámina dental activa (DL) que se encuentra en el área retromolar a los 5 o 6 años; los restos de la lámina dental del cordón gubernacular (GC), presentes por encima de los dientes en erupción (9).…”
Section: Células Madreunclassified
“…El término "bio-raíz" se refiere a una raíz creada por bioingeniería, que puede estar perfectamente integrada con los tejidos periodontales y el hueso alveolar, sobre la cual sea posible colocar una corona (3,15). La elaboración de una bio-raíz, pese a que no constituye un biodiente completo, podría ser una opción que solucione el problema de la regeneración del esmalte, ya que permitiría que una corona sintética sea soportada por una raíz de bioingeniería, considerando además que con los métodos protésicos actuales se puede reproducir perfectamente tamaño, forma y color de una corona natural (27,30).…”
Section: Bio-raícesunclassified
See 1 more Smart Citation